2012
DOI: 10.5562/cca2149
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects Concerning the Efficient Calculation of Vibrational Spectra beyond the Harmonic Approximation

Abstract: Abstract. This feature article discusses some selected aspects in the field of vibrational structure calculations based on vibrational self-consistent field, VSCF, and vibrational configuration interaction, VCI, theory. As the quality of such calculations depends strongly on the accuracy of the underlying multidimensional potential energy surface, PES, some techniques will be discussed to establish high-quality PESs in a fully automated manner. As an alternative to VCI theory multiconfiguration self-consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…A notably larger gain is found when moving to n = 3, where oc-VCC [3] gives an order of magnitude enhancement for all states except ν 1 with a significant reduction in MAD from 0.386 to 0.0712 cm −1 . oc-VCC[3pt4] achieves <0.1 cm −1 accuracy for all states and oc-VCC [4] further boosts the accuracy down to <0.01 cm −1 . Interestingly, the improvement of oc-VCC[n] over oc-VCI[n] is also significant after n = 3; the reduction in MAD, which is moderate for n = 2 (3.23 to 1.50 cm −1 ), is drastic for n = 3 (0.781-0.0712 cm −1 ).…”
Section: B Formaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…A notably larger gain is found when moving to n = 3, where oc-VCC [3] gives an order of magnitude enhancement for all states except ν 1 with a significant reduction in MAD from 0.386 to 0.0712 cm −1 . oc-VCC[3pt4] achieves <0.1 cm −1 accuracy for all states and oc-VCC [4] further boosts the accuracy down to <0.01 cm −1 . Interestingly, the improvement of oc-VCC[n] over oc-VCI[n] is also significant after n = 3; the reduction in MAD, which is moderate for n = 2 (3.23 to 1.50 cm −1 ), is drastic for n = 3 (0.781-0.0712 cm −1 ).…”
Section: B Formaldehydementioning
confidence: 99%
“…These results clearly demonstrate the advantage of using optimized coordinates for VCC. To better understand the nature of the enhanced accuracy beyond n = 3, the excitation level weights for VCI [4], VCC [4], oc-VCI [4], and VCC [4] are examined. (See Table SI in the supplementary material 52 for the whole data.)…”
Section: B Formaldehydementioning
confidence: 99%
“…Dipole surfaces as needed for the evaluation of infrared intensities were truncated after the 2D terms and were determined at the density fitting Hartree-Fock level. We have shown quite recently that this rather crude approximation yields results, which are not only qualitatively correct, but which are in good agreement with accurate results [5]. In a subsequent step, the potential being represented by grid points was transformed to polynomials up to 8th order.…”
Section: Computational Details For the Lithium Fluoride Clustersmentioning
confidence: 65%
“…Details of this procedure are presented elsewhere. Benchmark calculations for small lithium fluoride clusters [5], i.e. Li 2 F 2 , showed that the combination of density fitting explicitly correlated local coupledcluster calculations for the 1D and 2D terms and the modeling scheme for the 3D terms results in deviations of about one wavenumber in comparison to conventional coupled-cluster calculations for the 1D, 2D and 3D terms and are thus negligible.…”
Section: Computational Details For the Lithium Fluoride Clustersmentioning
confidence: 99%
See 1 more Smart Citation